Efficacy and Safety of High-Intensity Focused Ultrasound for Noninvasive Abdominal Subcutaneous Fat Reduction. Issue 2 (February 2020) - Hong, Ji Yeon; Ko, Eun Jung; Choi, Sun Young; Kwon, Tae-Rin; Kim, Jong Hwan; Kim, Soo Yeon; Kim, Beom Joon
Abstract : BACKGROUND: Demand for noninvasive body contouring has increased. OBJECTIVE: We evaluated the efficacy and safety of a thermal high-intensity focused ultrasound (HIFU) device for abdominal body shaping. PATIENTS AND METHODS: Adults with a body mass index ⩽30 kg/m 2 and an abdominal subcutaneous fat tissue thickness ≥2.5 cm were enrolled for HIFU treatment at energy levels of 150 J/cm 2 (first session) and 135 J/cm 2 (second session). The primary end point was a change from baseline waist circumference at post‐treatment Week 8. Secondary efficacy end points were: changes in body weight, waist/hip ratio, and fat thickness assessed by ultrasound, caliper, and a fat CT scan. The Global Aesthetic Improvement Scale was evaluated by both investigators and subjects. RESULTS: The primary assessment achieved statistical significance, showing a reduction of 3.43 cm in mean waist circumference. The treatment effect was cumulative, with a steady decrease in waist circumference and fat thickness. The mean pain scores immediately after treatment were 4.45 ± 2.74 on a scale of 1 to 10 with 10 being the most painful, which decreased to 1.10 ± 1.33 after 1 week. CONCLUSION: High-intensity focused ultrasound is an effective and safe treatment modality for reducing waist circumference in nonobese individuals with focal fat accumulation.